A study on green pretreatment of rice straw using Petha wastewater and Mausami waste assisted with microwave for production of ethanol and methane - Dolly Kumari; Yogita Jain; Radhika Singh (Energy Conversion and Management: X, 2021)
The present work proposes a new and novel pretreatment of rice straw (RS) using petha wastewater (PWW) and mausami waste (MW) for its conversion to ethanol and methane. This approach is an example of waste-to-waste pretreatment. The organic matter present in the RS has been utilized as the source for biofuel production by the action of the anaerobes present in the microbial culture utilized (cow dung). To enhance the production of biofuel, chemical and green pretreatment methods were compared with respect to solubilisation of the lignocellulosic content into reducible sugars. Maximum glucose release (292 mg/L) was obtained for 2% NaOH pretreated RS followed by PWW pretreatment (198 mg/L). Further 5 min. microwave pretreatment in addition to the above pretreatment methods were also used to enhance the glucose release for production of ethanol and methane. All reactors were operated for two batch runs. The maximum bioethanol yield was 28.75 mg/L (1150 mg/kgRS) for PWW and microwave pretreated RS and methane yield was 11.86% of total gas produced for PWW pretreated RS respectively. This study is based on preliminary experiments on RS with microwave assisted PWW and MW pretreatment for ethanol and methane production.